Cysteine Induced Chiral Morphology in Palladium Nanoparticle. (8th April 2019) - Cho, Nam Heon; Lee, Hye‐Eun; Ahn, Hyo‐Yong; Lee, Yoon Young; Im, Sang Won; Kim, Hyeohn; Nam, Ki Tae
Abstract: New morphology of palladium nanoparticles is demonstrated by utilizing the interaction of amino acid and palladium metallic surface. Chiral cysteine molecules induce chiral spiral structure evolution. The resulting spiral palladium nanoparticles show rotational direction preference with respect to the handedness of the added cysteine molecule. The strong correlation of the resulting morphologies with surfactant and cysteine concentration exists for effective generation of chirality. Synthesized chiral palladium nanoparticles are around 100 nm sized cubic based nanoparticles with each face of the cube containing a spiral structure. Generation of nanoparticle morphology is studied through growth of time‐dependent morphology evolution with statistical analysis of spiral structure formation. The reported synthesis method can provide a new route to nanomaterial design for enantioselective catalysis and sensing. Abstract : Chiral cysteine molecules induce chiral nanostructure evolution during seed‐mediated palladium nanoparticle synthesis in an aqueous environment. The resulting structure has spiral orientation which rotational direction has correlation with the handedness of input cysteine molecules. Synthetic conditions strongly affect the capability of cysteine molecules to guide morphology evolution.